132 Balance control in chronic ankle instability and healthy subjects: traditional analysis of centre of pressure displacement and nonlinear analysis of its variability. (3rd March 2020) - Esteves, José; Dinis, Ricardo; Fernandes, Orlando; Castro, Maria António; Oliveira, Raul; Correia, Pedro Pezarat
Abstract : Background: Many causes of chronic ankle instability (CAI) have been postulated and include deficits in proprioception, impaired neuromuscular firing patterns, reduced balance and postural control. Balance control can be studied with the traditional analysis of centre of pressure (CoP) displacement and nonlinear analysis of its variability. Objective: To compare balance control behaviour in CAI and healthy subjects, using the traditional linear and nonlinear variables for CoP displacement. Design: Comparative observational study. Setting: Laboratory. Patients (or Participants): Students from 2 universities in Lisbon, who volunteered to participate in this study: 16 subjects with chronic ankle instability and 20 healthy subjects. Selection was based on the International Ankle Consortium (IAS) selection criteria position statement. Interventions (or assessment of risk factors): The independent variable was the presence of CAI according to IAS selection criteria. Main outcome measurements: CoP displacement was measured on a force plate during single leg stance for 60 seconds, on stable and unstable surfaces. Balance control was measured through traditional variables of CoP displacement: total displacement; medio-lateral and antero-posterior displacement; amplitude of medio-lateral and antero-posterior displacement. Variability of CoP displacement measured with nonlinear variables: sample entropy of medio-lateral and antero-posterior displacement; correlation dimension of medio-lateral and antero-posterior displacement. Results: On stable surface, no differences between groups for all the traditional variables were found but correlation dimension of CoP medio-lateral displacement had lower values on CAI group with statistical significance (p<0, 05). On unstable surface no differences were found neither with traditional variables or variability nonlinear analysis. Conclusions: Besides no differences on most of variables, lower values of the correlated dimension of CoP displacement during one leg stance on a stable surface in CAI subjects may indicate a balance control system with less variability to adapt to the environment and the task demands. More studies are needed to continue the investigation about the balance control related to CAI.